Inclusionary housing : creating and maintaining equitable communities - Jacobus, Rick (Policy focus series (Lincoln Institute of Land Policy), 2015)
This report illustrates how local governments can realize the full benefit of inclusionaryhousing policies, which require developers of new market-rate real estate to providesome affordable units for lower-income residents. Policy makers, practitioners, and localleaders will learn how to build public support, use data to inform program design, establish reasonable expectations for developers, and ensure long-term program quality.